Healthy lifestyle changes favourably affect common carotid intima-media thickness: the Healthy Lifestyle Community Programme (cohort 2) - Christian Koeder; Sarah Husain; Ragna-Marie Kranz; Corinna Anand; Dima Alzughayyar; Nora Schoch; Andreas Hahn; Heike Englert (Journal of Nutritional Science, 2022)
Common carotid intima-media thickness (ccIMT) progression is a risk marker for cardiovascular disease (CVD), whereas healthy lifestyle habits are associated with lower ccIMT. The objective of the present study was to test whether a healthy lifestyle intervention can beneficially affect ccIMT progression. A community-based non-randomised, controlled lifestyle intervention was conducted, focusing on a predominantly plant-based diet (strongest emphasis), physical activity, stress management and social health. Assessments of ccIMT were made at baseline, 6 months and 1 year. Participants had an average age of 57 years and were recruited from the general population in rural northwest Germany (intervention: n 114; control: n 87). From baseline to 1 year, mean ccIMT significantly increased in both the intervention (0⋅026 [95 % CI 0⋅012, 0⋅039] mm) and control group (0⋅045 [95 % CI 0⋅033, 0⋅056] mm). The 1-year trajectory of mean ccIMT was lower in the intervention group (P = 0⋅022; adjusted for baseline). In a subgroup analysis with participants with high baseline mean ccIMT (≥0⋅800 mm), mean ccIMT non-significantly decreased in the intervention group (−0⋅016 [95 % CI −0⋅050, 0⋅017] mm; n 18) and significantly increased in the control group (0⋅065 [95 % CI 0⋅033, 0⋅096] mm; n 12). In the subgroup, the 1-year trajectory of mean ccIMT was significantly lower in the intervention group (between-group difference: −0⋅051 [95 % CI −0⋅075, −0⋅027] mm; P < 0⋅001; adjusted for baseline). The results indicate that healthy lifestyle changes may beneficially affect ccIMT within 1 year, particularly if baseline ccIMT is high.